FRI0569 Evaluation of bone microarchitecture in systemic sclerosis patients: relationships between trabecular bone score (TBS) and disease severity. (15th June 2017) - Paolino, S; Gotelli, E; Sulli, A; Ruaro, B; Ghio, M; Pizzorni, C; Alessandri, E; Tomatis, V; Seriolo, C; Molfetta, L; Cutolo, M; Casabella, A
Abstract : Background: Systemic sclerosis (SSc) is a rare connective tissue disorder characterized by an increased synthesis and deposition of extracellular matrix in the skin and internal organs (1). Several studies described SSc as potential risk factor for osteoporosis, however, to date the bone quality in SSc is unclear (2). Trabecular bone score (TBS) has been recently proposed as an indirect measure of bone microarchitecture (3). Objectives: The aim of this study was to assess bone microarchitecture in SSc patients and possible association with disease severity and microangiopathy. Methods: Twenty-three female SSc patients (mean age 63.2±12.8 SD years, mean disease duration 92.8±66 SD months, mean Raynaud's Phenomenon duration 142.6±126.1 SD months) were enrolled after written informed consent. The assessment of disease severity was performed using the Medsger's severity scale (4). Bone Mineral Density (BMD) measurements at L1-L4, femoral neck and total hip, were performed using DXA Prodigy Densitometer (GE Lunar). TBS was derived for each spine DXA examination using the TBS index (TBS iNsight Medimaps). Nailfold videocapillaroscopy (NVC) was used to assess the microangiopathy based on nailfold video capillaroscopic pattern (NVC) analysis and the microangiopathy evolution score (MES) (5–6). Using the FRAX (Fracture Risk Assessment Tool) we also evaluate the 10-year risk of hip and major joints osteoporotic fracture. Results: A positive correlation was observed between TBS and Medsger's general organ score (r=0.5; p=0.01); no other correlations were found between TBS and Medsger's score. Interestingly, TBS was positively and significantly correlated with modified Rodnam skin score (mRss) (p=0.01). When the patients were divided in two groups considering skin involvement by mRss, TBS was found significantly higher into the group with mRss >15 compared to the group with mRss <15 (1.255±0.08 vs 1.163±0.03; p=0.01) No correlations were found between NVC patterns/MES and bone quality assessment (TBS) or bone density assessment (BMD), only a significant correlation, as expected, was observed between MES and skin involvement (mRss) (p=0.05). On the other hands, FRAX, the major osteoporotic fracture risk, positively correlates with Medsger's kidney disease severity (p=0.04) and Medsger's lung disease severity (p=0.04); in addition, FRAX, for hip fracture risk, seems to correlate significantly with Medsger's lung involvement severity (p=0.04). Conclusions: This study demonstrates in SSc patients a relationship between clinical disease severity (organ fibrosis/failure) and altered bone microarchitecture (TBS). In addition, skin involvement was found significantly correlated with altered quality of the trabecular bone architecture (TBS) and a significant increase of osteoporotic fracture risk (FRAX) was found correlated with kindey and lung involvement. References: Varga J, Abraham D. J Clin Invest. 2007 Mar;117(3):557–67. Loucks J, Pope JE. Semin Arthritis Rheum. 2005 Feb;34(4):678–82. Silva BC et al. J Bone Miner Res. 2014 Mar;29(3):518–30. Medsger TA et al. Clin Exp Rheumatol. 2003;21(3 Suppl 29):S42–6. Sulli A, et al. Ann Rheum Dis 2008;67:885–7. Cutolo et al. J Rheumatol 2000; 27;155.60. Disclosure of Interest: None declared